A generalization of Tyler's M-estimators to the case of incomplete data - Gabriel Frahm; Uwe Jaekel (University of Cologne, Seminar of Economic and Social Statistics, 2009)
Many different robust estimation approaches for the covariance or shape matrix of multivariate data have been established until today. Tyler's M-estimator has been recognized as the 'most robust' M-estimator for the shape matrix of elliptically symmetric distributed data. Tyler's Mestimators for location and shape are generalized by taking account of incomplete data. It is shown that the shape matrix estimator remains distribution-free under the class of generalized elliptical distributions. Its asymptotic distribution is also derived and a fast algorithm, which works well even for high-dimensional data, is presented. A simulation study with clean and contaminated data covers the complete-data as well as the incomplete-data case, where the missing data are assumed to be MCAR, MAR, and NMAR.
Keywords: H12; H20; 330; covariance matrix; distribution-free estimation; missing data; robust estimation; shape matrix; sign-based estimator; Tyler's M-estimator